The Elements Of Coastal Public Open Space - P.P. Egam; A.H. Thambas; F. Siregar; J.O Waani; R. Lakat (Eduvest - Journal of Universal Studies, 2023)
Aspec of strategic value of coastal areas has the potential to be developed to the fullest The reality shows that public open spaces on the coast at the research site appear as they are and do not have strong characteristics in both social and physical aspects. The mixing of activities makes the elements of open space faint and difficult to recognize functionally. The purpose of the study was to find the constituent elements of public open space on the coast and identify the concept of coastal public open space arrangement. This type of research is descriptive qualitative so that it can explain in detail the phenomenon as well as physical data and activities through social interactions that occur at the research location. The results showed that coastal public spaces as spaces for social interaction and economic activity can be a driver of public activities freely by the community. The open space element adapts to the existence of coastal public spaces so that it becomes a concept in the arrangement of coastal public spaces. Natural elements as drivers of free interaction while artificial elements as drivers of economic activity